Evaluation of Chronic Kidney Disease Progression in Dogs With Therapeutic Management of Risk Factors - Perini-Perera, Sofía; Del-Ángel-Caraza, Javier; Pérez-Sánchez, Alicia Pamela; Quijano-Hernández, Israel Alejandro; Recillas-Morales, Sergio (Frontiers in Veterinary Science, 2021)
This research was performed to describe the characteristics of the progression of naturally occurring chronic kidney disease (CKD) in dogs, together with the management of identified risk factors, following the International Renal Interest Society recommendations. Dogs diagnosed and staged with CKD, and with a longitudinal follow-up from the moment of diagnosis of up to a maximum of 730 days, were included. A total of 545 dogs that presented risk factors for the development CKD were analyzed, out of which 36 met the inclusion criteria. Advanced age was identified in 80.6% of cases. Initiation risk factors were represented by inflammatory/infectious diseases, history of anesthetic-surgical procedures, heart disease, neoplasms, endocrinopathies and exposure to nephrotoxic drugs. During the follow-up period, progression of CKD was identified in 47.2% of the cases, being more salient in advanced stages. A significant difference between the survival curves in early and advanced CKD stages was observed. The factors related to decreased survival were hyperphosphatemia, anemia, and low body condition score. No differences were found between the presence of arterial hypertension and renal proteinuria, and decreased survival. This study observed a relationship between early CKD diagnosis and the positive impact risk factors therapeutic management. Furthermore, CKD diagnosis based on the persistent finding of abnormalities in early disease markers, such as serum symmetric dimethylarginine increase and/or renal proteinuria, and timely therapeutic management of risk factors, allowed for CKD stabilization, reducing progression to advanced stages, and favoring higher survival rates.